Children as Research Subjects: The Ethical Issues (Bangladesh Journal of Bioethics, 2015)
From the very beginning of civilization, children are made the subject matter of many social and clinical researches. Due to the vulnerabilities of physical frailty and mental immaturity, childrens interests and rights need to be protected from the risks associated with any kind of research. Recently, there has been increased global concern towards the involvement of children in research for the protection of their rights by the ethical research practice. It emphasizes upon the ongoing nature of ethical considerations that ethical issues need to be considered throughout the research process and even the post research ethical issues are equally significant. The study explores some of the major ethical issues that arise in research involving children during and after the research in terms of the best interests of the children.Bangladesh Journal of Bioethics 2015 Vol.6 (1): 6-10